The Influence of the Implementation of the Government’s Internal Control System on the Quality of Financial Statements and its Implications for Financial Accountability of the Regional Government at Bandung, Indonesia - Mulyati, Yati; Christine, Debbie; Arwati, Dini; Arifian Rachman, Andry (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to test and analyze the influence of the government’s internal control system on the quality of financial statements and its implications on the financial accountability of the regional government in Bandung, Indonesia. The type of this research is explanatory research. The population in this research is government agencies in Bandung. Data was collected by using interview and questionnaire techniques, and then the data was analyzed by using path analysis. The results of this research indicate that: 1) The government’s internal control system influences the quality of financial statements; 2) The government’s internal control system and the quality of financial statements influence the financial accountability of regional governments.